Metrics are the key: development of criteria and indicators for measuring sustainability in international chemicals management - Blum, Christopher; Zeschmar-Lahl, Barbara; Heidbüchel, Esther; Stolzenberg, Hans-Christian; Kümmerer, Klaus; Becker, Anna Isabel; Friege, Henning (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Materials and products provided by the chemical industry and related sectors are indispensable for a satisfactory living standard and high standard of health. On the other hand, emissions from resource extraction, production, unsustainable use, and inadequate disposal of chemicals and related products contribute significantly to the pollution of the planet. To address the aforementioned issues on a global level, the “Global Framework on Chemicals” was launched in 2023. It presents a comprehensive plan with 28 targets jointly addressing the lifecycle of chemicals. In addition to efforts to ensure the sound management of chemicals and waste, the targets are partially oriented towards the concept of sustainable chemistry due to its search for innovative and sustainable solutions across the complete value chain of chemicals. To enable and monitor the implementation of this framework, indicators are needed to show progress towards the targets. This paper presents indicators that are based on an internationally established understanding of sustainable chemistry. To consider the target relevance of each indicator as well as its suitability, criteria were developed to assess the viability of the proposed indicators. The criteria as well as the suggested indicators were discussed with international experts and in stakeholder workshops that involved all six UN regions. The evaluation of these meetings ultimately led to a set of 23 indicators based on the previously defined criteria. It is demonstrated that these indicators can be used to measure the progress towards the targets of the Global Framework on Chemicals.